43.8k views
5 votes
3(2x-2)=6(x-1)
How do you do this

1 Answer

3 votes

Answer:


\large\bf\implies{infinitely \:many\: solutions}

Alternate forms :


\large \bf \implies{x \in ( - \infty \: , \infty)}

Explanation:


\bf \longrightarrow{3(2x - 2) = 6(x - 1)}

  • Apply the Distributive Property


\bf \longrightarrow{6x - 6 = 6x - 6}

  • Rearrange variables to the left side of the equation


\bf \longrightarrow{6x - 6x = - 6 + 6}

  • Apply the inverse property of addition


\bf \longrightarrow{0 = 0}

  • Bases on the given conditions, the (system of) equation(s) has


\bf \longrightarrow{infinitely \:many\: solutions}

User Dbuchet
by
5.8k points